SKELETAL BANDING PATTERN AND GROWTH RATES OF THE MASSIVE CORAL Porites lutea Edwards & Haime ON THE NORTH COAST OF CENTRAL JAVA, INDONESIA - Supriharyono . (JOURNAL OF COASTAL DEVELOPMENT, 1998)
Growth rates (linear skeletal extension) and the timing of skeletal band formation were measured in 15 speciments of the massive coral. Porities lutea at three locations on the north coast of Central Java. The result of skeletal X-rayed indicate that timing of the high density (HD) and low density (LD) bands is synchronous at three locations. A one year growth is characterized by three HD bands, one of which is usually wider. Comparisons of the skeletal extention rates (X-ray radiography) indicate that the growth rates of P.lutea are statistically lower at the Menjangan Kecil island when compared to Bandengan Bay (p<0.01) and Panjang island (p< 0.05).